Reprovação escolar no campus Amílcar Ferreira Sobral: em busca das suas causas - Santos, Lígia Beatriz da Costa e Silva Ribeiro (2005)
Concern with the increasing rate of failure at the Amílcar Ferreira Sobral Campus - CAFS - from 1999 to 2004 (50% on high school senior's first year in 2003) is the reason for the research on the probable reasons for such a problem. CAFS is related to the Federal University of Piauí - UFPI, located in the city of Floriano. It works with three different courses: The equivalent in Brazil to Senior High School, the Preparatory Course on Agricultural Techniques and the Technical Course on Nursing. 445 students enrolled in 2004. Among these, 324 answered the questionnaire to which they were submitted; that represents 72.8 % of the total amount of students. The procedures for the survey were: a literary review, questions about methods and teaching techniques, personal information about the students, documentary analysis made by teachers through their class diary, notes made by the school counseling board, as well as interviews with two different groups of students that didn't get to pass their exams. The information contained in the questionnaires was analyzed through SPSS for Windows, version 8.0. It shows the predominance of single girls among the students, whose most parents have graduated from High School. Parents and students have minor participation on the school's activities and few really cultivate the habit of reading. The family income varies from R$300 to 600 in most families. The causes for school failure are basically associated to social cultural issues; the lack of motivation or interest is not only the students' responsibility, but can be also expressed by the social, cultural and familiar context in which they are inserted, as well as by the educational system, the school and the teachers' performance. From this point, it became possible to figure out what was already demonstrated by science. Of course, results on research about the subject are ali debatable, for it's impossible to establish a universal standard for a problem that involves such multidetennined, multidimensioned and complex phenomena, in permanent interaction with its context, as a result of conflict and contradiction, in an ongoing transformation process, always articulated with multiple interests and significance. Fighting against these obstacles is the current challenge. It requires an educator who's aware of the people's rights, that understands that Education is one of the greatest means of both personal and collective growth for humanity and that such a professional is top important for the human kind to reach its destiny and be happy. The result in this research shows that the reasons for school failure at CAFS are, according to some students, related to the lack of basis and some issues associated with teaching methods and techniques, as well as evaluation procedures. It is believed that such work, even inserted in a small field of research, compared with the size of the country is capable to offer a fundamental contribution to the academic/educational environment, which gives space to new research on pedagogic problems and educational policy.